2020
DOI: 10.1080/21556660.2020.1841495
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and associated factors of medication administration error among nurses working in Amhara Region Referral Hospitals, Northwest Ethiopia

Abstract: Introduction: Medication administration errors are common health problems that threaten patient safety and raise mortality rates, duration of hospital stay, and cost of services. It also influences healthcare professionals performing the procedure and healthcare organizations. Its prevalence in Ethiopia is high ranging from 51.8% to 90.8%. Objective: This study aimed to assess the magnitude and associated factors of medication administration error among nurses at Northwest Amhara Region Referral Hospitals. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
3
12
0
9
Order By: Relevance
“…Bivariate and multivariate logistic regression analysis was used to identify factors associated with medication administration error reporting. Variables with p < 0.02 in bivariate logistic regression analysis were entered to multivariate logistic regression analysis [ 13 ]. The adjusted odds ratio was used to interpret the strength of association at 95% CI and those variables with p < 0.05 in multivariate logistic regression analysis were considered as significant predictors of the outcome variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bivariate and multivariate logistic regression analysis was used to identify factors associated with medication administration error reporting. Variables with p < 0.02 in bivariate logistic regression analysis were entered to multivariate logistic regression analysis [ 13 ]. The adjusted odds ratio was used to interpret the strength of association at 95% CI and those variables with p < 0.05 in multivariate logistic regression analysis were considered as significant predictors of the outcome variable.…”
Section: Methodsmentioning
confidence: 99%
“…ere are a lot of studies done on MAE [12][13][14][15][16][17], but to the knowledge of the researcher, there are only a few studies [10,11] reporting whether those MAEs are reported or not among nurses in Ethiopia. In developing countries like Ethiopia, educational, economic, and trained manpower problems, the issue is primarily one of the least investigated and neglected health problems [18].…”
Section: Introductionmentioning
confidence: 99%
“…Among those 81 hospitals in the region, the University of Gondar, Dessie, Felege-Hiwot, Tibebe-Ghion, Debre-Markos, Waldiya, Debre Tabor, and Debebirhan are referral hospitals. The number of healthcare workers in these hospitals was estimated to be 4,002 [21,22].…”
Section: Study Settingmentioning
confidence: 99%
“…(22) Entretanto, ressaltam-se alguns estudos que apresentaram abordagem mista (individual e sistêmica) no gerenciamento do erro. (23,24) Isso pode representar um avanço para a mudança de paradigma quando da ocorrência de erros no trabalho em saúde. A cultura punitiva encontra-se em transição, ao passo que os trabalhadores da saúde percebem a finalidade não punitiva da notificação do erro.…”
Section: Discussionunclassified